Evolutionary intelligence : how technology will make us smarter - Neuman, W. Russell (Cambridge, UK : The MIT Press, 2023)
"Ubiquitous computational technologies will define our future, and this book takes the hopeful view that such technologies, properly designed, can enhance rather than diminish human agency. As people co-evolve with our technology, we can develop technological assistance to enhance our decision making and compensate for our biases: personalized medicine, intelligent romance, digital law, hybrid athletics, and cyberfinance offer compelling cases of how augmented intelligence is working now and how it will continue to evolve"--
Evolutionary intelligence -- Communication like never before : how would E.I. actually work? -- The hard part : compensating for human cognitive bias -- Here be dragons -- Evolutionary intelligence in historical perspective -- Evolutionary intelligence is already here -- Putting evolutionary intelligence to work : some brief case studies -- Next steps.
Includes bibliographical references and index.
Keywords: Technology and civilization; Evolutionary; Human beings -- Effect of technological innovations on; Human-computer interaction; Computational intelligence